Student learning strategies, mental models and learning outcomes in problem-based and traditional curricula in medicine. - Lycke KH; Grøttum P; Strømsø HI (Medical Teacher, 2006)
Kelson and Distlehorst (2000) state the PBL outcomes should be discussed on a broad basis including a useable knowledge base, skills in problem solving, self-directed learning and collaboration. The present research compares students in a PBL programme and in a traditional program on learning strategies, mental models and outcomes. Learning strategies and metal models of learning were measured for two student groups in 2001 using an adaption of Vermunt's (1994) 'Inventory of learning styles'. Learning outcomes were measured for the same groups in 2002 using a test of medical knowledge. PBL-students showed significantly more self-regulated learning and more constructive conceptions of learning. No significant differences in learning outcomes were found between the two groups. Students in the PBL-programme perceived students as more active contributors to group learning process and made use of a broader range of resources than students in the traditional programme. The findings confirm effects of educational programmes on student learning strategies (Vermetten 1999) and also confirm lack of significant differences in medical knowledge (Albanese 2000, Colliver 2000, Norman & Schmidt 2000, Wiers-Jensen & Aasland 2004). The curricular influence on students' learning strategies challenges educators to design approaches that promote lifelong learning skills as well as disciplinary knowledge.